Curious about George : Curious George, cultural icons, colonialism, and US exceptionalism - Schwartz-DuPre, Rae Lynn (Race, rhetoric, and media series., 2021)
"In 1940, Hans Augusto Rey and Margret Rey built two bikes, packed what they could, and fled wartime Paris. Among the possessions they escaped with was a manuscript that would later become one of the most celebrated books in children's literature-Curious George. Since his debut in 1941, the mischievous icon has only grown in popularity. After being captured in Africa by the Man in the Yellow Hat and taken to live in the big city's zoo, Curious George became a symbol of curiosity, adventure, and exploration. In Curious about George: Curious George, Cultural Icons, Colonialism, and US Exceptionalism, author Rae Lynn Schwartz-DuPre argues that the beloved character also performs within a narrative of racism, colonialism, and heroism. Using theories of colonial and rhetorical studies to explain why cultural icons like Curious George are able to avoid criticism, Schwartz-DuPre investigates the ways these characters operate as capacious figures, embodying and circulating the narratives that construct them, and effectively argues that discourses about George provide a rich training ground for children to learn US citizenship and become innocent supporters of colonial American exceptionalism"--